Redesign of Taman Lansia Bandung as a Therapeutic Garden - Sugih Pradifta, Fachmy; Mutia Ekasari, Astri; Qodariah, Siti; Damayanti, Verry; Ayu Gayatri, Ega; Ernanda Pramadhika, Muhammad; Shafa Anifa, Deby (KnE Social Sciences, 2023)
Elderly group needs to be paid attention to while redesigning an inclusive city by improving their quality of life to achieve successful aging. The existence of elderlyfriendly urban spaces is imperative in promoting mental health and well-being in the scarcity of open spaces in dense urban environments. These spaces can help them to actively maintain health, physical and cognitive functions, and involve with the social environment. Taman Lansia Bandung is one of the thematic parks whose initial purpose was to become an elderly-oriented open space. However, Taman Lansia Bandung felt to be less and less accommodating to the elderly’s comfort and ironically provides more attractions for younger visitors to the park. This paper attempts to propose a new design for Taman Lansia with a systematic design approach. A site analysis was conducted to examine the spatial issues such as natural, man-made, physical, and perceptual attributes to develop the contextual design idea. A set of design principles and criteria are generated from a systematic literature review of case studies, related research, and technical standards on accessible design for the elderly and disabled. The result of site analysis and design principles are then formulated into a design vision of the park. A 3D-model was created to simulate the design idea and then compare it with the existing conditions with the photo-match technique. The result is a therapeutic garden that improves the elderly’s psychological comfort with a more ergonomic design, closeness to nature, and a multisensory impulse experience. Keywords: elderly park, therapeutic garden, green open space design, urban landscape, urban spaces